Detection of Imatinib Based on Electrochemical Sensor Constructed Using Biosynthesized Graphene-Silver Nanocomposite - Wu, Zhen; Liu, Jingjing; Liang, Minmin; Zheng, Haoyue; Zhu, Chuansheng; Wang, Yan (Frontiers in Chemistry, 2021)
The establishment of a monitoring technique for imatinib is necessary in clinical and environmental toxicology. Leaf extracts of Lycoris longituba were used as reducing agents for the one-step synthesis of reduced graphene oxide-Ag nanocomposites. This nanocomposite was characterized by TEM, FTIR, XRD and other instruments. Then, the graphene/Ag nanocomposite was used as a modifier to be cemented on the surface of the glassy carbon electrode. This electrode exhibited excellent electrochemical sensing performance. Under the optimal conditions, the proposed electrode could detect imatinib at 10 nM-0.28 mM with a low limit of detection. This electrochemical sensor also has excellent anti-interference performance and reproducibility.